MACHINE TRANSLATION WITH JAVANESE SPEECH LEVELS’ CLASSIFICATION - Nafalski, Andrew; Wibawa, Aji Prasetya (Informatyka, Automatyka, Pomiary w Gospodarce i Ochronie Środowiska, 2016)
A hybrid corpus-based machine processing has been developed to produce a proper Javanese speech level translation. The developed statistical memory-based machine translation shows significantly accurate results. Integration of an automatic text classifier and an expert system is proposed to help Javanese in classifying the speech levels used for a specific interlocutor. Javanese rule-based expert system is designed while naive Bayes classifier is selected after outperforming simple logic probability approach. As a result, the average of translation accuracy (72.3%) indicates that the integrated intelligent interfaces could effectively solve the Javanese language pragmatic translation problems.